Bichronous online learning: L2 learners' perceptions - Nor Dawirah Rahman; Sabariah Abd Rahim; Bernadette Tobi; Mohammad Aqmal Hafidz Musa (Global Academic Excellence, 2020)
English educators worldwide have been implementing multifarious online learning tools to teach students English, especially since the Covid-19 arrival. Researches on and adoption of online learning have vigorously increased since then to explore the effectiveness of umpteen online learning tools to ensure students get the best of education. With this regard, this paper looked into L2 learners’ perceptions towards bichronous online learning - a mixed mode of online learning in tertiary education and employed a quantitative method via questionnaire focusing on eliciting respondents’ perceptions on bichronous online learning, the challenges they faced while learning bichronously and the suggestions they proposed to improve bichronous online learning. The respondents involved were 30 first-year students taking the Essential Communication Skills course at Universiti Malaysia Sabah. In recapitulation, the findings portrayed positive perceptions of L2 learners towards bichronous online learning. It was also highlighted that poor internet connection, poor time management and lack of motivation were the core challenges of the blended mode while suggestions to enhance it were mainly on the use of multitudinous learning methods, more interactive platforms and creation of a conducive learning environment. These findings served as a foundation for devising suitable bichronous online learning materials for learning English effectively.